Analysis of the sealing performance and creep behavior of the inner casing of a 1000 MW supercritical steam turbine under bolt relaxation. (November 2015) - Wang, Weizhe; Liu, Yingzheng
Abstract: The creep behavior and sealing performance of the inner casing of a 1000 MW supercritical steam turbine were investigated during 200, 000 h of steady operation at high temperatures. The influence of the stress relaxation of bolts on creep behavior and sealing performance was specifically demonstrated. A constitutive creep model based on continuum damage mechanics and a multiaxial creep strain formula was used to describe the stress–strain behavior and calculate the multiaxial strain. Due to significant bolt relaxation in the high-temperature region, stress in the steam inlet region decreased dramatically; likewise, multiaxial creep strain decreased markedly in this region. Contact pressure significantly decreased during the first 10, 000 h, especially in the regions between bolts 1 and 9, and the largest decrease in contact pressure exceeded 340 MPa. This reduced sealing performance at high temperatures. Further comparison of the contact pressure and the opening displacement at the contact surface was carried out with and without bolt relaxation. The massive difference of 153 MPa between these two cases in the primary creep phase demonstrated that bolt relaxation significantly influences sealing performance. Highlights: Multiaxial creep strain formula is established to calculate the multiaxial strain. Influence of the bolt relaxation on the creep behavior of inner casing is studied. Sealing performance of the inner casing under bolt relaxation is fully demonstrated.